2014
DOI: 10.2478/s11686-014-0243-1
|View full text |Cite
|
Sign up to set email alerts
|

First detection of acalculous cholecystitis associated with Sarcocystis infection in a patient with AIDS

Abstract: Acalculous cholecystitis and cholangitis are increasingly being recognized as complications of AIDS. The opportunistic parasites that have been most commonly associated with these disorders are Cryptosporidium species, Isospora belli, Cyclospora cayetanensis and Enterocytozoon bieneusi. The authors performed a parasitological survey on the gallbladder tissue sections of patients underwent cholecystectomy due to chronic acalculous cholecystitis at the Shiraz University of Medical Sciences, Iran. Light microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Only a few studies have discussed the host's immune response against Sarcocystis spp. From the reported cases, it was obvious that infection elicits a strong eosinophilic and T cell-mediated response [11]. In vivo, experimental infection results suggested that S. neurona and S. calchasi might be able to down-regulate the interferon-γ (IFN-γ) signaling pathway [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have discussed the host's immune response against Sarcocystis spp. From the reported cases, it was obvious that infection elicits a strong eosinophilic and T cell-mediated response [11]. In vivo, experimental infection results suggested that S. neurona and S. calchasi might be able to down-regulate the interferon-γ (IFN-γ) signaling pathway [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse biliary cystoisosporiasis has been also reported in a West African man who presented with acute illness and dilated bile ducts, and unknown HIV status [17]. The first case of Sarcocystis-related human non-calculous cholecystitis worldwide was reported in 2014 in an AIDS patient [4].…”
Section: Discussionmentioning
confidence: 98%
“…Also, during a histopathologic review of the gallbladder, infection with Cystoisospora belli was diagnosed on sections stained with hematoxylin and eosin and then confirmed by a C. belli-specific nested PCR of recuts from the paraffin block [4].…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…The paucity of clinical disease among residents in areas where outbreaks have been noted amongst foreigners suggests that the infection stimulates a humoral (yet T-cell-mediated) memory. However, there is only one single case report in the literature [ 7 ] on an AIDS patient in an advanced stage of immunosuppression with concomitant sarcocystosis, manifesting itself atypically as an acalculous cholecystitis; suggesting, apart from an eosinophilic reaction, a role for T-cell-mediated defense. In immune-competent individuals developing disease, the average cytokine production seems to decrease as a sign of early-phase immunosuppression.…”
Section: Biology Epidemiological Immunological and Clinical Featurmentioning
confidence: 99%